PERAN GOOD CORPORATE GOVERNANCE DALAM MEMODERASI PENGARUH PROFITABILITAS, LIKUIDITAS, LEVERAGE TERHADAP TAX AVOIDANCE - Purwaningrum, Supiningtyas; Wijaya, Radhicka A.; Natalina, Ary; Kakiay, Agustina Nicke (Gapenas Publisher, 2024)
The main objective of this study is to analyze the role of Good Corporate Governance (GCG) in moderating the influence of Profitability, Liquidity, and Leverage on Tax Avoidance. This study uses secondary data sourced from the Indonesia Stock Exchange (IDX) website. The research population is LQ45 companies listed on the IDX that have published financial and annual statements for the 2020-2023 period. A total of 16 companies were selected as samples over a period of 4 years, resulting in 56 data points, based on purposive sampling techniques. This study uses a quantitative research methodology. To test the hypothesis, a moderation regression analysis was carried out using EViews 10 software with a significance level of 5%. The results of the study show that Liquidity and Leverage have a significant effect on Tax Avoidance, while Profitability does not. Furthermore, the GCG variables represented by Institutional Ownership succeeded in moderating the relationship between Profitability, Liquidity, and Leverage with Tax Avoidance